2001
DOI: 10.1136/adc.85.4.286
|View full text |Cite
|
Sign up to set email alerts
|

Should children with developmental and behavioural problems be routinely screened for lead?

Abstract: Aim-To test the hypothesis that children with behavioural and/or developmental problems have significantly higher blood lead concentrations than the general childhood population. Methods-Blood samples were taken from 69 children with behavioural and/or developmental problems and 136 controls (children admitted for elective day case surgery under general anaesthetic). Blood lead estimations were carried out using graphite furnace atomic absorption Results-Children with behavioural and/or developmental problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 14 publications
1
19
0
1
Order By: Relevance
“…In general, the mean blood lead level is estimated to be below 5 g/dl in Western European countries and between 5 and 10 g/dl in Eastern ones. Lewendon et al report that up to 5% of the children in England have blood lead levels >10 g/dl (Lewendon et al 2001). Other studies showed that average concentrations of cord blood from healthy children were between 2.02 g/dl and 3.83 g/dl in Poland, 4.82 g/dl in Czechoslovakia, 4.09 g/dl in Taiwan and 2.49 g/dl in our study (Durska et al 2002;Truska et al 1989;Soong et al 1991).…”
Section: Discussionmentioning
confidence: 97%
“…In general, the mean blood lead level is estimated to be below 5 g/dl in Western European countries and between 5 and 10 g/dl in Eastern ones. Lewendon et al report that up to 5% of the children in England have blood lead levels >10 g/dl (Lewendon et al 2001). Other studies showed that average concentrations of cord blood from healthy children were between 2.02 g/dl and 3.83 g/dl in Poland, 4.82 g/dl in Czechoslovakia, 4.09 g/dl in Taiwan and 2.49 g/dl in our study (Durska et al 2002;Truska et al 1989;Soong et al 1991).…”
Section: Discussionmentioning
confidence: 97%
“…88 However, in a study of children drawn from a population at low risk for lead exposure, a series of 43 children with either developmental delay or attention deficit hyperactivity disorder did not demonstrate elevated lead levels compared to controls (class II study). 89 Current consensus guidelines with respect to lead testing in children recommend a strategy of targeted screening of all children with identifiable risk factors.…”
Section: What Is the Role Of Lead And Thyroid Screening In Children Wmentioning
confidence: 99%
“…Currently, about 3% of children in the US have elevated blood levels of lead (more than 10 μg/dL); however, recent data show that the effect on cognitive skill in children could occur at lower levels, even as low as 5 μg/dL. Children absorb over three times as much as adults and are at greatly increased risk through increased activity such as chewing objects and sucking their fingers [22]. Blood lead levels in children with neurological disorders is on the higher side due to excessive hand-to-mouth activity, poor nutritional status consequent to feeding difficulties, poor appetite, and social neglect.…”
Section: Discussionmentioning
confidence: 95%